2014
DOI: 10.1002/pon.3505
|View full text |Cite
|
Sign up to set email alerts
|

Negative religious coping as a correlate of suicidal ideation in patients with advanced cancer

Abstract: Objective The purpose of this study is to examine the relationship between negative religious coping (NRC) and suicidal ideation in patients with advanced cancer, controlling for demographic and disease characteristics and risk and protective factors for suicidal ideation. Methods Adult patients with advanced cancer (life expectancy ≤6 months) were recruited from seven medical centers in the northeastern and southwestern USA (n = 603). Trained raters verbally administered the examined measures to patients up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 55 publications
(77 reference statements)
4
43
0
8
Order By: Relevance
“…The growing literature showed mixed results on the association between religious coping and cancer distress (Trevino et al 2014;Rohani et al 2015;Zamanian et al 2015). In a systematic review of 17 studies examining religious/spiritual coping strategies in cancer adjustment, Thuné-Boyle et al (2006) found seven of the studies showed some evidence for the beneficial effect of religious coping, with one study showing religious coping to be detrimental in a subgroup of their population.…”
Section: Introductionmentioning
confidence: 98%
“…The growing literature showed mixed results on the association between religious coping and cancer distress (Trevino et al 2014;Rohani et al 2015;Zamanian et al 2015). In a systematic review of 17 studies examining religious/spiritual coping strategies in cancer adjustment, Thuné-Boyle et al (2006) found seven of the studies showed some evidence for the beneficial effect of religious coping, with one study showing religious coping to be detrimental in a subgroup of their population.…”
Section: Introductionmentioning
confidence: 98%
“…According to a study conducted in Iceland suicidal behaviour was after a cancer diagnosis (AOR = 1.6, 95% CI 1.4-1.9). The risk increase was greatest immediately after diagnosis; during the rst year after diagnosis (AOR = 2.5, 95% CI 1.7-3.5) and thereafter diagnosis (AOR = 1.5 95% CI 1.2-1.8) [14].…”
Section: Introductionmentioning
confidence: 92%
“…Meanwhile, Ahmadi et al proposed that spiritual closeness to God or a superior power was the most important factor for adjustment to cancer (Ahmadi and Ahmadi, 2015). The results obtained by Trevino et al show that people with negative or religious beliefs are more prone to psychological distress and risk of suicide (Trevino et al, 2014). …”
Section: Introductionmentioning
confidence: 95%
“…Yet, Zemestani et al reported lower levels of social adjustment in cancer patients compared to healthy people (Zemestani et al, 2013). Previous studies have reported that there are many factors associated with adjustment in cancer patients (Trevino et al, 2014). Charmaine et al (2016) found medication therapy, rest, relaxation, and distraction to be effective for adjustment to physical problems, while social support and religion were important for adjustment to psychological problems (D'Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%